Creation of new tomato forms with fungal disease resistance genes based on marker selection - I. N. Shamshin; E. V. Grosheva; M. V. Maslova; R. M. Samoilova (Овощи России, 2021)
Relevance. The presented studies are aimed at obtaining new forms of tomato with a complex of genes for resistance to fungal diseases in combination with a standard type of bush and dark coloring of fruits based on marker-mediated selection.Methodology. The biological objects of the study are varieties and hybrid forms of tomato from the collection of the Michurinsky SAU. Molecular genetic analysis was performed using the following methods. DNA extraction was carried out from young leaves using a kit for isolation of NC Sample NC manufactured by Agrodiagnostika LLC according to the manufacturer's protocol. Fermentas production kits were used for PCR. Identification of the cladosporosis resistance gene was Cf-19 performed using the DNA marker R7. The presence of a fusarious wilting resistance gene was determined by a I-2/5 marker. The amplification results were visualized by agarose gel electrophoresis.Results. During the research, a collection of varieties and hybrid forms of tomato of the Michurinsky GAU was analyzed in order to identify genes for resistance to cladosporiosis Cf-19 and fusarium wilt I-2. A total of 52 genotypes were analyzed. It was found that most samples (41 samples) are characterized by a heterozygous state of the Cf-19 gene. All indeterminant and semi-determinant forms had both alleles. Of the 23 determinant forms presented in the collection, 10 had only one allele corresponding to recessive homozygote. Among all analyzed tomato genotypes, no dominant homozygous forms were noted. The study of the collection revealed several alleles of the I-2 gene. In total, four fragments corresponding to various alleles were amplified. A total of 50 resistant genotypes have been identified in the collection. Two alleys of the I-2 gene (633/693 bp) were identified in 42 tomato samples. Four varieties are homozygous in one allele (633 bp), which determines resistance. Three varieties have a second resistance allele (566 bp). One genotype has only an allele defining susceptibility (693 bp). On the basis of molecular analysis, as well as an assessment of the type of bush and fetal color, initial forms were selected with subsequent hybridization. 67 hybrid tomato plants were obtained. Evaluation of the presence of resistance genes showed that most of the resulting hybrids are resistant to cladosporiosis and fuzariosis. This is due to the presence of dominant alleles of Cf-19 and I-2 genes in a heterozygous state. Among the resulting hybrids, plants with a bark type of bush were identified. A total of 13 such plants were obtained.Conclusion. Thus, the work carried out allowed to obtain hybrid forms of tomato combine the signs of resistance to two pathogens of fungal diseases and the stem type of the bush. These forms are planned to be used in further selection work.